26 - EFFECTS OF HIGH-VOLTAGE CURRENT ON EDEMA, IN RATS PAW PRODUCED BY NERVE COMPRESSION (Fiep Bulletin - online, 2011)
Among the complications of the sciatic nerve compression, we can mention the lower limb edema formation. As a resource, to reduce edema, has highlighted the use of high voltage pulsed current. However, there is a gap with respect to their use in reducing edema that comes from nerve compression. This work aimed to evaluate the effects of current high voltage on the paw edema of rats, produced by an experimental model of sciatica. We used 24 rats divided into 3 groups: GS – placebo treatment; GP+ - treated with anodic current, GP- - treated with cathode current. The model consisted of nerve tie nerve compression in four distinct regions, with catgut thread. The evaluation was carried out by volumetry, with immersion of the foot in a cylinder with a syringe, the water was removed until the water level returned to initial state. The evaluations occurred before surgery to postoperative day 3, before and after the simulation or realization of the 1st treatment, after 5 and 10 days of treatment. No 3 PO, began the treatment, daily for 10 consecutive days, 20 minutes each. For the application of high voltage current on the incision, the animals were anesthetized and positioned in lateral lying. The current intensity used was 10% lower than the motor threshold. The results showed significant increase for all groups when comparing pre-and post-stimulation, with the time pre-injury, but there were no differences between pre-injury with 5 and 10 days. By comparing the time pre-stimulation with the following, only the sham was significantly decreased in 5 and 10 days. It is concluded that the methodology used, no beneficial effects of edema reduction, with the high voltage current.
Keywords: Transcutaneous Electric Nerve Stimulation; Sciatica; Edema